2013
DOI: 10.1002/pssa.201329281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silane functionalized sodium titanate nanotubes and their influence on thermal and mechanical properties of epoxy nanocomposite

Abstract: Sodium titanate nanotubes (NaTiNTs) were prepared by hydrothermal method and functionalized with three different silane coupling agents. The existence of the chemical bond between silane molecules and nanoparticles was confirmed by scanning electron microscopy (SEM) equipped with electron dispersive X-ray spectroscopy (EDS) mapping, Fourier transform infrared (FTIR) spectroscopy, and simultaneous differential scanning calorimetry-thermogravimetric analysis (DSC-TGA). NaTiNTs before and after functionalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…by the controlled hydrolysis of trialkoxysilanes (e.g. Si(EtO) 3 R) in anhydrous solvents to link any organic group via a strong Ti-O-Si-C bond [76] or by esterification with carboxylic acids in anhydrous alcohol [77]. The linked organic groups may then serve as a template for subsequent chemical reactions, e.g.…”
Section: Physical and Chemical Properties Of Titanate Nanomaterialsmentioning
confidence: 99%
“…by the controlled hydrolysis of trialkoxysilanes (e.g. Si(EtO) 3 R) in anhydrous solvents to link any organic group via a strong Ti-O-Si-C bond [76] or by esterification with carboxylic acids in anhydrous alcohol [77]. The linked organic groups may then serve as a template for subsequent chemical reactions, e.g.…”
Section: Physical and Chemical Properties Of Titanate Nanomaterialsmentioning
confidence: 99%
“…Covalent functionalization is beneficial when anisotropic layered titanates are used as polymer fillers. Brnardic et al reported 7 °C higher glass transition temperature and 10.4% higher storage modulus in epoxy composites loaded with 3 wt% silanized titanate nanotubes [143].…”
Section: Modificationmentioning
confidence: 97%
“…This anchors the R chain onto the titanate by a strong Ti-O-Si-C bond. The primary use of this reaction is covalent hydrophobization, however, if the R group is reactive enough then it can also serve as a bridgehead for further organic functionalization steps and subsequent polymer grafting for nanocomposite applications [142][143][144]. The surface -OH groups can enter an esterification reaction with carboxylic acids in anhydrous alcohol [145].…”
Section: Modificationmentioning
confidence: 99%
“…The composite material obtained was tested in light-emitting devices realizing a new class of device with promising improved mechanical and thermal properties without affecting the optoelectronic performance of the device [4]. Brnardić and co-workers report the synthesis, by a hydrothermal method, and functionalization of sodium titanate nanotubes (NaTi-NTs) [5]. Addition of low concentrations of NaTi-NTs to an epoxy resin resulted in an increase in the glass transition temperature (T g ) and storage modulus (E′) of the epoxy, and interestingly, the combustion properties, specifi cally the heat release rate (HRR) of the [6].…”
Section: Dear Readersmentioning
confidence: 99%